A fully packaged self-powered sensor based on near-field electrospun arrays of poly(vinylidene fluoride) nano/micro fibers - Y.-K. Fuh; S.-Ch. Li; Ch.-Y. Chen; Ch.-Y. Tsai (eXPRESS Polymer Letters, 2018)
Energy harvesting devices based on the triboelectric and piezoelectric principles have been widely developed to scavenge wasteful and tiny mechanical energy into usable electrical energy. In particular, triboelectric energy harvesting generators with relatively simpler structure and piezoelectric fiber-based counterpart with extremely light weight compositions showed a very promising application in the self-powered sensors. In this paper, a novel hybridization of graphenebased piezoelectric generator (GBPG) and graphene-PET triboelectric generator (GPTG) were simultaneously packaged. The integrated structure, graphene-based hybridized self-powered sensor (GHSPS), was demonstrated to be optically transparent and mechanically robust. For the piezoelectrically harvesting device, an in-situ poling and direct-write near-field electrospinning (NFES) Poly(vinylidene fluoride) (PVDF) piezoelectric fibers were fabricated and integrated with a single layer chemical vapor deposition (CVD) grown graphene. On the other hand for GPTG counterpart, two composite layers of a single layer graphene/PET simultaneously served as triboelectrically rubbing layers as well as bottom/top electrode. This GHSPS successfully superimposed both piezoelectric and triboelectric electricity and the synergistically higher output voltage/current/power were measured as ~6 V/280 nA/172 nW in one press-and-release cycle of finger induced motion. The proposed GHSPS showed a promising application in the field of self-powered sensors to be ubiquitously implemented in the future Industry 4.0 scenarios.